2021
DOI: 10.3390/biomedicines9080961
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Lentiviral Gene Delivery of HLA-DR and Vaccination of Humanized Mice for Improving the Human T and B Cell Immune Reconstitution

Abstract: Humanized mouse models generated with human hematopoietic stem cells (HSCs) and reconstituting the human immune system (HIS-mice) are invigorating preclinical testing of vaccines and immunotherapies. We have recently shown that human engineered dendritic cells boosted bonafide human T and B cell maturation and antigen-specific responses in HIS-mice. Here, we evaluated a cell-free system based on in vivo co-delivery of lentiviral vectors (LVs) for expression of a human leukocyte antigen (HLA-DRA*01/ HLA-DRB1*04… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Recently, we showed an alternative lentivirus-based approach to deliver the expression of HLA-DR4. LV were used systemically to introduce HLA-DR4 and hGM-CSF/hIFN-α/HCMV-gB in huNRG mice, enhancing B-cell development compared to animals that did not receive the LV injection (Kumar et al , 2021). Therefore, a plausible explanation is that the NRG background seems to be fitter to promote B cell development than the NSG strain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we showed an alternative lentivirus-based approach to deliver the expression of HLA-DR4. LV were used systemically to introduce HLA-DR4 and hGM-CSF/hIFN-α/HCMV-gB in huNRG mice, enhancing B-cell development compared to animals that did not receive the LV injection (Kumar et al , 2021). Therefore, a plausible explanation is that the NRG background seems to be fitter to promote B cell development than the NSG strain.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups demonstrated that humanization of transgenic NSG- and NRG-derived strains expressing human class I and class II MHCs/HLAs, as expected, showed improvements in T-cell development and cytotoxic functions (Najima et al , 2016; Danner et al , 2011; Majji et al , 2016; Masse-Ranson et al , 2019; Suzuki et al , 2012). Due to the difficulties of generating transgenic mice with several different HLA alleles, we explored lentiviral vector (LV) in vivo delivery of HLA-DRB1*04:01 (DR4) into huNRG mice (Kumar et al , 2021). Upon co-administration with LV expressing human GM-CSF/IFN-α and gB, we observed activation of T-cell and B-cell development (Kumar et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this mouse strain is more resistant to irradiation than NSG strains, mice can be irradiated with higher doses (i.e., 450 cGy). Frequencies of human immune cell subsets in peripheral blood are determined around 15 to 17 weeks after cell transplantation using flow cytometry and antibody panels similar to the protocols used in NSG mice [ 48 , 49 , 50 , 51 , 52 ].…”
Section: Humanization Protocolsmentioning
confidence: 99%
“…Several studies have used HIS NRG mice to model HCMV infection and immune response [ 48 , 51 , 52 , 82 ]. In this model, HCMV reactivation by treatment with recombinant human G-CSF promoted the detection of the virus in the spleen, lymph nodes, liver, salivary glands and bone marrow.…”
Section: Viral Infections In Nsg and Nrg Humanized Mouse Modelsmentioning
confidence: 99%